Social relationship modulates advisor’s brain response to advice-giving outcome evaluation: Evidence from an event-related potential study - Zhang, Can; Tao, Ruiwen; Zhao, Hanxuan; Zheng, Kexin; Dai, Mengge; Xu, Sihua (Frontiers in Neuroscience, 2022)
Advice-giving is a double-edged sword in social interaction, which could bring benefits or considerable losses for the advisee. However, whether the social relationship affects the time course of advisor’s brain response to outcome evaluation after the advice-giving remains unclear. In the present study, we used event-related potentials (ERPs) to investigate the modulation of social relationships on advisor’s outcome feedback processing after the advice-giving and related neural activities. The results showed larger feedback-related negativity (FRN) to a loss than to a gain both when the friends accepted and rejected the advice, whereas this effect only existed when the strangers rejected the advice, but not when they accepted it. In contrast, the P3 results demonstrated the enhanced neural sensitivity when the strangers accepted the advice than rejected it despite leading to a loss, while a larger P3 amplitude was found when the friends accepted the advice than rejected it and brought a gain. The theta oscillation results in the friend group revealed stronger theta power to loss when the advisee accepted the advice than rejected it. However, this effect was absent in the stranger group. These findings suggested that outcome evaluation in advice-giving was not only influenced by feedback valence and social reward, but also modulated by social relationships.